PENANGANAN PERBEDAAN INDIVIDUAL DALAM PROSES PEMBELAJARAN STENOGRAFI - Aprilia, Lin (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2013)
ABSTRACTThe research objectives are: (1) to investigate any factors influencing individual difference in the stenography learning process; (2) to investigate any methods used by teachers in handling individual difference; (3) to investigate any hindrances faced by teachers in the individual difference handling, (4) to investigate teachers? efforts to cope with any hindrances in handling individual difference. This research is conducted in a qualitative approach. The sources of data comprise informants, research site, as well as documents and archieves. Based on the data analysis, it can be concluded that: (1) the factors influencing individual difference are: differences in family background, cognitive or intelligence, learning readiness, students? perception and interest in stenography as a subject; (2) teachers? methods to in handling are giving counselling to students, modifying various teaching methods, establishing amall peer groups in the classroom, being aware of students? competence difference, implementing modul learning system, givin aperception before starting stenography learning, giving home assignments for students to be well-prepared of the materials; (3) the hindrances in handling are the learning process is conducted classically so that proper guidance can not be done maximally, it is difficult to determine the most appropriate teaching method, it ias also difficult to pay a close attention to students? competence difference because o their large number in a class, not every students can understand modul system learning, students barely listen thoroughly to teachers? aperception, and they sometimes do not accomplish stenography tasks geven to them; (4) Teachers? efforts to cope with the hindrances in handling individual difference in the stenography learning processare giving conselling to them during school hour break, asking for students? feedback, establishing peer groups based on students? learning interest, doing some approach and communication to students in the classroom, giving personal guidance, underpinning students in the aperception process, and monitoring students? learning activities. Keywords: individual difference, teachers? handling, Stenography subject matter.